Growth and yield of tropical maize landraces and commercial genotypes in Yucatan, Mexico: Yield of tropical maize cultivars - da Conceicao-dos Santos, Luis Filipe; Ruíz-Sánchez, Esaú; Garruña-Hernández, René; Andueza-Noh, Rubén Humberto (Ecosistemas y Recursos Agropecuarios, 2024)
The state of Yucatan, known for its shallow Leptosol soils poses challenges to agriculture. Therefore, this study focused on examining ecophysiological attributes influencing the growth and yield determinants of six maize genotypes. The study assessed vegetative characteristics, growth rates, dry matter allocation, grain yield, and harvest index. All maize genotypes exhibited early maturity, a favorable trait under the climate conditions of Yucatan. Most genotypes exhibited superior growth rate and dry matter content when compared to the landrace Elotillo. Stem and grain were identified as the primary organs for dry matter accumulation, with 36% and 22% respectively. The highest grain yield was noted in hybrids Impacto and DK-390. This study provided valuable information for farmers in selecting suitable maize genotypes in Yucatan, although additional evaluations of different genotypes and management conditions are recommended.
Keywords: dry matter; grain yield; growth rate; leptosols; zea mays